Lepanthes miraculum (Orchidaceae), a new addition to the Peruvian orchid flora - Collantes, Benjamín (2016)
Lepanthes miraculum, formerly known from one area in Bolivia, is reported from Machu Picchu in southern Peru. Illustrations, figures, notes on the specimens found in Peru and an updated description are provided and compared to those known from Bolivia.